2000
DOI: 10.1128/iai.68.7.4018-4023.2000
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Streptococcus sanguinis in the Oral Cavity of Infants: Evidence for a Discrete Window of Infectivity

Abstract: The heterogeneous group of oral bacteria within the sanguinis (sanguis) streptococci comprise members of the indigenous biota of the human oral cavity. While the association of Streptococcus sanguinis with bacterial endocarditis is well described in the literature, S. sanguinis is thought to play a benign, if not a beneficial, role in the oral cavity. Little is known, however, about the natural history of S. sanguinis and its specific relationship with other oral bacteria. As part of a longitudinal study conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1
20

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(207 citation statements)
references
References 34 publications
(46 reference statements)
6
180
1
20
Order By: Relevance
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).Several other studies have focused on the in vitro relationship between S. sanguinis and some of the periodontal pathogens. Hillman et al (1985) showed that, in samples from oral sites where S. sanguinis was detected, Tannerella forsythia was present in 1 % of the cases, and in samples where S. sanguinis was not detected, Tannerella forsythia was present in 10 % of the oral sites.…”
mentioning
confidence: 99%
“…S sanguis seems to have an antagonistic relationship with S mutans as far as adhesion and colonization are concerned. 18 In the presence of S sanguis, the binding sites of S mutans on the salivary pellicle formed on the bracket are reduced. Our results would thus seem to be consistent with the theory that S sanguis acts as an antagonistic bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…The antagonism between S. mutans and streptococci of the mitis group, particularly S. sanguins and S. gordonii, at the ecological level has been well-documented (26). Epidemiological studies revealed that high levels of S. mutans are always concurrent with low levels of S. sanguinis (27), whereas high levels of S. sanguinis in the oral cavity correlate with delayed S. mutans colonization (28). Recent work by Kreth et al (29) showed sophisticated interspecies interactions between these two species that might play an essential role in balancing competition and coexistence within the oral community.…”
Section: S Mutansmentioning
confidence: 99%